The Role of Legislative and Executive Institutions Based on the 1945 Constitution in Realizing the Sustainable Development Goals (SDGs) - Franciscus Xaverius Wartoyo; Shillo, Verlyn Adelaide Tzuriel; Sigrid, Stephanie; The, Jennifer (Jurnal Smart Hukum (JSH), 2025)
The Sustainable Development Goals (SDGs) have become a target for member countries of the United Nations (UN), including Indonesia. Achieving the SDGs as a global development agenda requires the active role of various parties, including legislative and executive institutions. Collaboration between the two institutions is a strategic key in realizing the SDGs as well as the ideals of the Indonesian state contained in the 4th paragraph of the Preamble of the 1945 Constitution, namely protecting the entire Indonesian nation, advancing general welfare, educating the nation's life, and participating in implementing world order based on independence, eternal peace and social justice. This study aims to analyze the forms of collaboration between legislative and executive institutions in supporting the implementation of SDGs in Indonesia. This study uses a qualitative approach by analyzing policies, regulations, and collaborative practices between the two institutions. The results show that structured and long-term goal-oriented synergies are needed to maximize the implementation of the country's ideals and the SDGs. This study recommends increased collaboration between the legislative institution as a regulator and watchdog of executive performance, and the executive institution as the implementer.